VINES AND ART - Eugeniu ALEXANDROV; Vasile BOTNARI; Boris GAINA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Each nation constituting its cultural identity is based on several symbols, customs, legends, religious beliefs, etc., which leave its mark on the development of society. One of the commonly used symbols is also the vine. In all times the painters were overwhelmed by the vine, the gift of the gods. On the canvases of the great masters of the past and of the present we see compositions related to the cultivation of the vine, as well as the production of wine. Over the course of his life, man struggled to make his own living space and beautify his living space. Still in the Stone Age, our ancestors were drawing bison, horses, tigers, mammoths and other animals on the walls of the cave. These were the first steps of mankind in the development of art. With the emergence of the first civilizations and the first cities, various techniques of expressing everything that is beautiful and capable of provoking positive emotions have developed.